Science level 2(the city school) (Albakio International,The City school Lahore, 2012)
This curriculum module focuses on building upon students' existing scientific knowledge and skills. It delves deeper into various scientific concepts and emphasizes problem-solving abilities. In the realm of life science, students explore the diversity of life, genetics, and the intricacies of human anatomy and physiology. Physical science concepts such as the properties of matter, chemical reactions, electricity, and magnetism are investigated in greater detail. Finally, the module explores Earth science topics, including plate tectonics, weather patterns, and the solar system.